Birth defects data from hospital-based birth defect surveillance in Guilin, China, 2018–2020 - Yang, Xingdi; Zeng, Jianjuan; Gu, Yiping; Fang, Yiming; Wei, Caiyun; Tan, Shengkui; Zhang, Xiaoying (Frontiers in Public Health, 2022)
Objectives Birth defects (BDs) are a major contributor to perinatal and infant mortality, morbidity and lifelong disability worldwide. A hospital-based study on birth defects was designed in Guilin city in the Guangxi province of Southwestern China aiming to determine the prevalence of BDs in the studied region, and the classify the BDs based on clinical presentation and causation. Methods The study involved BDs among all pregnancy outcomes (live births, stillbirths, death within 7 days, and pregnancy terminations) born in the 42 registered hospitals of Guilin between 2018 and 2020. The epidemiological characteristics of BDs and the etiologic profile of BDs were evaluated in this study. Results Of the total 147,817 births recorded during the study period, 2,003 infants with BDs were detected, giving a total prevalence rate of 13.55 per 1,000 births. The top five BD types were congenital heart defects, polydactyly, syndactyly, malformations of the external ear, and talipes equinovarus, whereas, neural tube defects, congential esophageal atresia, gastroschisis, extrophy of urinary bladder, were the least common BD types in these 3 years. Only 8.84% of cases were assigned a known etiology, while most cases (91.16%) could not be conclusively assigned a specific cause. Conclusion This study provides an epidemiological description of BDs in Guilin, which may be helpful for understanding the overall situation in Southwest China of BDs and aid in more comprehensive studies of BDs in future healthcare systems, including funding investment, policy-making, monitor, prevention. Strong prevention strategies should be the priority to reduce BDs and improve the birth quality.